Avaliação gerontológica na atenção primária à saúde: atividades cotidianas segundo o índice de Katz - Brito, Irisdalva França Soares (2021)
Evaluating the independence on the activities of elederly people’s daily life   is necessary for a correct planning and direction of care actions, both in terms of prevention and rehabilitation. Home visits were carried out to 231 elderly and applied a questionnaire about sociodemographic information and the Katz index. Although the majority of the elederly have been evaluated as independent for the daily life activities, it was possible to identify situations which need active intenvention in order to postpone inability.